Proceedings of International Symposium on Sensor Networks, Systems and Security : advances in computing and networking with applications, in honor of Dr. S.S. Iyengar's 70th birthday /: advances in computing and networking with applications, in honor of Dr. S.S. Iyengar's 70th birthday. (2018) - Unknown
No abstract available